PENYULUHAN DAMPAK PENGGUNAAN ENERGI KOTOR BATU BARA - Nofrima, Sanny; Pratiwi, Winda (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2023)
The presence of coal mining has resulted in landscape change, reduced soil fertility, threats to biodiversity, reduced water quality, reduced air quality and environmental pollution. This service aims to understand and track awareness of dirty coal energy use in Palembang, one of the oldest cities, as the lack of understanding of coal's impact on local communities has led to a very serious disease outbreak. A coal-producing city in Indonesia. The approach used was to educate the community on the impacts of coal. Through these socialization activities, public awareness of the impacts can be obtained.